Friction and Structural Responses of Ion Implanted Polyoxymethylene Copolymer (POM-C) - Rahman, Md. Shahinur; Lyakhov, Konstantin; Yang, Jong-Keun; Uddin, Muhammad Athar; Chowdhury, Muhammad Sifatul Alam (Rajshahi University Journal of Science and Engineering, 2016)
Polyoxymethylene copolymer (POM-C) round block was implanted with 120 KeV ions of He to doses of 5 x 1016 and 1 x 1016 ions cm-2. It was also implanted with 120 KeV ions of Ar + He and He + Ne to dose of 1 x 1016 ions cm-2, respectively. The friction coefficient behavior of both implanted and unimplanted POM-C blocks was investigated using a ball on disk tribometer mechanism. The friction coefficient of He ion implanted POM-C block at a dose of 5 x 1016 ions cm-2 is lowest compared to all unimplanted and others ions doses implanted POM-C blocks. It also shows the moderate surface texturing (atomic rearrangement), lower surface micro-hardness and average surface roughness compared to both unimplanted and other ions doses implanted POM-C blocks due to well adjusted carbonization, cross-linking and ions-target atoms collisions, which is ascertained from SEM-EDS, Raman spectroscopic and surface profiling observations. The other ions doses implanted POM-C blocks demonstrate the higher friction coefficient and surface roughness with polymer surface deformation (crazing, cracking, pitting and gas evolution, bond breaking) due to severe chain scission, surface dose delivered atomic displacements and chemical structural degradation. It is concluded that the variation in friction coefficient behavior of POM-C block resulted from its structural response for ion beam implantation on the top surface.